Gustav Mahler/Uri Caine: Urlicht/Primal light - Mahler, Gustav 1860-1911; Caine, Uri (München Music edition winter & winter, 1997)
Very few, if any, attempts to merge classical music and jazz have succeeded. Somehow, jazz pianist Uri Caine's masterful and magnificent interpretations of selected works of the 19th century classical composer Gustav Mahler work remarkably well. Of course, it does not hurt to work with a stellar ensemble, including trumpeter Dave Douglas, violinist Mark Feldman, clarinetist Don Byron, and drummer Joey Barron, and turntable spinner DJ Olive, among others. However, it is Caine's clever arrangements that take the cake. He does not simply "jazz up" Mahler, which would mock the greatness of his works. Instead, he worms himself inside the songs and harmonies and uses them as a starting point to create a related, but new, synthesis of his music. Jewish folk melodies, cantorial renditions, free jazz, and classical violin are all merged in a whole that transcends the parts.